Addressing gaps on risk and resilience factors for alcohol use outcomes in sexual and gender minority populations. (13th April 2016) - Talley, Amelia E.; Gilbert, Paul A.; Mitchell, Jason; Goldbach, Jeremy; Marshall, Brandon D. L.; Kaysen, Debra
Abstract: Issues: In 2011, the Institute of Medicine released a report that constituted the first comprehensive effort by a federal body to understand the current state of science pertinent to the health needs of sexual and gender minority populations. This mini‐review summarises recent empirical, methodological and theoretical advances in alcohol‐related research among to lesbian, gay, bisexual and transgender (LGBT) populations and highlights progress towards addressing gaps, with a particular interest in those identified by the Institute of Medicine report. Approach: Articles published since 2011 were identified from PsycINFO and PubMed database searches, using various combinations of keyword identifiers ( alcohol, alcohol abuse, substance abuse, LGBT, lesbian, gay, bisexual, transgender ). Reference sections of included articles were also examined for additional citations. Key Findings: Recent empirical work has contributed to a greater understanding of sub‐group differences within this diverse population. Evidence has supported theorised influences that can account for alcohol‐related disparities, yet important gaps remain. Studies that examine the role of gender identity and its intersection with sexual identity within transgender and gender non‐conforming sub‐populations are lacking. Methodological advances in this literature have begun to allow for examinations of how minority‐specific and general risk factors of alcohol misuse may contribute to patterns of alcohol involvement over time and within social‐relational contexts Conclusions: The recommendations made in the current mini‐review are meant to facilitate future collaborative efforts, scale development, thoughtful methodological design and analysis and theoretically driven nuanced hypotheses to better understand, and ultimately address, alcohol‐related disparities among sexual and gender minority populations. [Talley AE, Gilbert PA, Mitchell J, Goldbach J, Marshall BDL, Kaysen D. Addressing gaps on risk and resilience factors for alcohol use outcomes in sexual and gender minority populations. Drug Alcohol Rev 2016;35:484–493]